The Iraqi EFL University Learners’ Abilities in Blended Education at Corona Virus Time - Betti , Mohammed Jasim; Saeed, Abdullah Algum (Journal of Ecohumanism, 2024)
The COVID-19 pandemic affected many aspects of daily life notably the educational system in the world including Iraq. Studying the effects of online English as a Foreign Language (EFL) instruction is essential in the light of the COVID-19 pandemic’s emergence and expansion as well as the move in education toward online courses. This study is concerned with the Iraqi EFL university learners’ abilities in blended education at Corona Virus time. Therefore, the study seeks to find answers for the following questions: 1) what is the effect of blended education on the Iraqi EFL ability? 2) what are differences in effect between online teaching and paper and pencil exam in blended teaching? The aims of this study include analyzing the effect of blended education on the Iraqi EFL ability and stating the differences in effect between online teaching and paper and pencil exam in blended teaching. Documents, which represent a very useful methodological instrument is the data collection method used in this study. The data consists of examinations in years (2020–2021 / 2021–2022) in the department of English, College of Education for Human Sciences, University of Thi-Qar. More than 200 Iraqi EFL students are included in the sample for this study. The study concludes that, there are no differences among the results of language, linguistics, literature, educational and non-departmental course in the online teaching /testing in the blended education. Over the course of the three paper-and-pencil exam sessions (2020-2021) the percentage of EFL learners’ results began to decline with verification in the type of materials. The percentages of success in online teaching are also very high, and all subjects were taught in a blended learning. Online teaching and learning, whether as pure or in blended education had a negative impact on students’ comprehension skills; the students were unable to understand the material when taking classes electronically. It is evident that a considerable percentage of students failed in the three paper and pencil subjects (drama, linguistics, and grammar), which were taught in a face-to-face way. Years of online learning caused the students to lose their capacity for memorization.